Kepribadian (Five Factor Model) dan Psychological Distress pada Mahasiswa Penerima dan Bukan Penerima Beasiswa - Natasya Julietta Rizky; Christina Hari Soetjiningsih (Faculty of Psychology, Universitas Semarang, 2021)
Scholarship recipient students have more demands and responsibilities than non-scholarship students. The demands of lectures can put pressure on students that can trigger psychological distress. Each individual is different in assessing the stress experienced depending on the personality. The research instrument used the NEO Five-Factor Inventory-3 scale and the Hopkins Symptom Checklist-25 scale (HSCL-25). The results of the comparison test show that there is no difference between recipients and non-scholarship recipients. The results of the correlation test show that there is a significant positive relationship between neuroticism and psychological distress, while extraversion and conscientiousness have a significant negative relationship with psychological distress. However, there is no significant relationship between openness to experience and agreeableness to psychological distress.